Transition of care and quality of life among people with stomas - Carolina Meneguetti; Jéssica de Aquino Pereira; Eliete Maria Silva (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To assess the quality of the transition from hospital to home care and the quality of life of people with stomas. Method: A cross-sectional study conducted with 84 patients from the Hospital de Clínicas of the Universidade Estadual de Campinas, after surgery for a stoma. The Care Transitions Measure and Stoma-QoL instruments were applied by telephone between April 2022 and August 2023. Descriptive and analytical statistical analysis was performed. Results: The total score of the Care Transitions Measure was 65.18±9.18. “Care plan” had the highest score (66.97±12.27) and “Understanding of medications” the lowest (63.82±10.45). The Stoma-QoL instrument score was 50.43±11.50. The domain “Social relationships outside family and close friends” had the highest mean score, while “Need for rest during the day” had the lowest mean score. Conclusion: The transition of care was assessed as moderate, suggesting potential implications for quality of life, especially regarding social aspects, perceived safety in the use of devices and willingness to carry out daily activities.